(untitled) - Conley, Dalton (New York, 2013)
The “untextbook” that teaches students to think like a sociologist.You May Ask Yourself gives instructors an alternative to the typical textbook by emphasizing the “big ideas” of the discipline, and encouraging students to ask meaningful questions. Conley employs a “non-textbook” strategy of explaining complex concepts through personal examples and storytelling, and integrates coverage of social inequality throughout the text.
Keywords: Sociology,Sociology,Xã hội học,Xã hội học; Methodology,Study and teaching,Phương pháp học,Dạy và học